Pengaruh Model Pembelajaran Discovery Learning Terhadap Minat Belajar Siswa dalam Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII SMP Negeri 1 Sianjur Mulamula Kecamatan Sianjur Mulamula Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Rame Febrianti Simanullang; Binur Panjaitan; Oktober Tua Aritonang; Lince Sihombing; Wilson Simanjuntak (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The purpose of this research is to find out whether there is an influence of the Discovery Learning Learning Model on Interest in Learning Christian Religious Education and Characteristics of Class VIII Students of SMP Negeri 1 Sianjur Mulamula, Sianjur Mulamula District, Samosir Regency, Academic Year 2023/2024. The method used in this research is a quantitative method with a pre-experimental research type with a